Cost‐effectiveness and budget impact of interferon‐free direct‐acting antiviral‐based regimens for hepatitis C treatment: the French case. Issue 10 (4th May 2016) - Deuffic‐Burban, S.; Obach, D.; Canva, V.; Pol, S.; Roudot‐Thoraval, F.; Dhumeaux, D.; Mathurin, P.; Yazdanpanah, Y.
Summary: We evaluated the cost‐effectiveness and the budget impact of new DAA‐based regimen use in France. A Markov model simulated chronic hepatitis C (CHC) treatment interventions with IFN‐based and IFN‐free regimens at stage of fibrosis ≥F3, ≥F2 or regardless of fibrosis stage, and treatment either with the least or the most expensive combination. It estimated quality‐adjusted life years (QALYs) and incremental cost‐effectiveness ratios (ICERs). It also assessed the budget impact over 5 years of treating all CHC‐screened patients, regardless of fibrosis, assuming ≤20 000 patients treated/year and priority to ≥F3. Sensitivity analyses were also conducted. For genotypes (G) 1–4, the initiation of IFN‐free regardless of fibrosis was a cost‐effective strategy compared to prior standard of care (SOC) initiated at stage F2: €40 400–88 300/QALY gained in G1; similar results were obtained for patients infected with G4. Considering G2–3, the most cost‐effective strategy was IFN‐based regimens regardless of fibrosis compared to prior SOC initiated at stage F2: €21 300 and €19 400/QALY gained, respectively; the strategy with IFN‐free regimens being more effective but not cost‐effective at current costs. The budget impact of treating all CHC‐screened patients over 5 years would range between 3.5 and 7.2 billion €, depending on whether one considers the least or the most expensive combination of new DAAs and whether one treats G2–3 with IFN‐based or IFN‐free new DAAs. In France, treatment initiation with new DDAs regardless of fibrosis stage is cost‐effective, but would add 3.5–7.2 billion € to an already overburdened medical care system.